Conflicts among councillors in the local government authorities: A tale of Msalala District Council - Swai, Idda Lyatonga; Uhahula, Faraja Cosmas; Ndesekio, Vicent Evarist; Nyakega, Chacha Timasi; Igulu, George (African Journal of Governance and Development, 2024)
A paper submitted to the African Journal of Governance and Development Volume 12 Issue 2 of December 2023